THE FORMATION AND DEVELOPMENT OF ORGANIZATION'S RELATIONSHIP WITH CONSUMERS IN THE CONTEXT OF MODERN CONDITIONS OF SOCIO-ECONOMIC ENVIRONMENT - T. N. Zhukova (Дискурс, 2017)
The article analyzes modern trends in socio-economic development and their impact on theory and practice of marketing. The author characterizes modern tools of relationship management of the enterprise with customers and prospects of new marketing methods.